2016
DOI: 10.1038/srep35889
|View full text |Cite
|
Sign up to set email alerts
|

A multimodality imaging model to track viable breast cancer cells from single arrest to metastasis in the mouse brain

Abstract: Cellular MRI involves sensitive visualization of iron-labeled cells in vivo but cannot differentiate between dead and viable cells. Bioluminescence imaging (BLI) measures cellular viability, and thus we explored combining these tools to provide a more holistic view of metastatic cancer cell fate in mice. Human breast carcinoma cells stably expressing Firefly luciferase were loaded with iron particles, injected into the left ventricle, and BLI and MRI were performed on days 0, 8, 21 and 28. The number of brain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

6
3

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 19 publications
0
28
0
Order By: Relevance
“…By engineering cells to express a luciferase reporter, bioluminescence imaging (BLI) can provide a direct readout of cell viability in dividing cell populations. Overall, as recently described 18 , combining our highly sensitive cellular MRI tools and BLI yields complementary information on the fate of metastatic cancer cells in preclinical models. As others have pointed to a role of the immune system in CTR/CTE and differences in primary tumour effects have been seen across models of the same cancer type 8 , the purpose of this study was to apply our multimodality imaging tools to study whether CTR/CTE effects are present in the syngeneic 4T1 immune competent mouse model of breast cancer metastasis.…”
Section: Introductionmentioning
confidence: 73%
“…By engineering cells to express a luciferase reporter, bioluminescence imaging (BLI) can provide a direct readout of cell viability in dividing cell populations. Overall, as recently described 18 , combining our highly sensitive cellular MRI tools and BLI yields complementary information on the fate of metastatic cancer cells in preclinical models. As others have pointed to a role of the immune system in CTR/CTE and differences in primary tumour effects have been seen across models of the same cancer type 8 , the purpose of this study was to apply our multimodality imaging tools to study whether CTR/CTE effects are present in the syngeneic 4T1 immune competent mouse model of breast cancer metastasis.…”
Section: Introductionmentioning
confidence: 73%
“…In fact, many rats displayed a decrease in BLI signal while tumor volume continued to increase or remained stable. Previous studies have reported a linear relationship between tumor volume and BLI signal for glioma models, whereas other studies have shown a lack of a relationship ( 35 – 39 ). In particular, Jost et al reported a small subset of animals ( n = 2) showing decreased BLI signal despite increasing tumor volume and contributed it to hemorrhage and necrosis ( 39 ).…”
Section: Discussionmentioning
confidence: 87%
“…While we acknowledge that there is potential for immune cell uptake of the iron oxide nanoparticles that may be released by dead cancer cells, we believe that the majority of the signal voids that remain present are live cancer cells retaining iron. For example, in Parkins et al [39] we investigated this mouse model using luciferase-positive 231BR cells and measured a strong correlation on day 0 between the number of signal voids detected in day 0 brain MR images and the brain signal measured in bioluminescence images, which is only detected from viable cells, providing evidence that signal voids represent live iron-labeled cells. In Hamilton et al [41] we used fluorescence activated cell sorting ( FACS) to successfully isolate live 231BR cells that were GFP-positive and labeled with red fluorescent (Flash Red) MPIO from the brains of mice.…”
Section: Discussionmentioning
confidence: 99%